Effects of psychosocial factors on Swedish waste collectors musculoskeletal pain through the mediating roles of occupational fatigue and physical demands: a structural equation model - Wenchu Huang; Xu Jin; Longao Yang; Yidan Dong; Yun Wang; Lihua He; Liyun Yang; Mikael Forsman (BMC Public Health)
Abstract Background Musculoskeletal pain is waste collectors’ most common non-fatal and disabling health problem. However, research on how psychosocial factors affect musculoskeletal pain via physical and psychosocial pathways is limited. This study aimed to examine the effects of leadership quality, social support, and job demands on musculoskeletal pain among Swedish waste collectors. In addition, the mediating roles of physical demands and occupational fatigue and their chain mediation were also examined. Methods A 2015 cross-sectional survey of all Swedish waste collectors utilized validated scales (COPSOQ II, SOFI-20, Nordic Questionnaire) to assess exposures (psychosocial factors), mediators (occupational fatigue, physical demands), and outcomes (musculoskeletal pain). Of 1005 eligible workers (≥ 1 year experience), 662 analyzed (65.9% response rate). Participants (median age = 47 years, IQR = 34–54; mean BMI = 27.1 ± 4.0 kg/m2) were primarily male (96.4%), operated rear-loader trucks (77.8%), and had 1–10 years of work experience (54.8%). Structural equation modeling and bias-corrected bootstrapping were used to assess direct/indirect pathways, with p ≤ 0.05 or 95% bootstrapped CIs excluded zero taken as significant. Results Occupational fatigue explains the majority of the intermediate processes. Specifically, occupational fatigue mediated the effects of job demands (β = 0.185, 95% CI: 0.134–0.246), leadership quality (β = -0.074, 95% CI: -0.123 - -0.031), and social support (β = -0.051, 95% CI: -0.095 - -0.007) on musculoskeletal pain. Physical demands mediated job demands (β = 0.113, 95% CI: 0.075–0.155) and leadership quality (β = -0.038, 95% CI: -0.077 - -0.003) on musculoskeletal pain. Physical demands also amplified occupational fatigue (β = 0.369, p < 0.001), forming a chain mediation pathway. Conclusions Leadership quality and job demands significantly influenced musculoskeletal pain through the mediating roles of occupational fatigue and physical demands, respectively. Social support’s impact was limited to occupational fatigue mediation. Physical demands may translate to occupational fatigue and be linked to musculoskeletal pain. Managers of waste collectors should prioritize leadership training and the construction of good psychosocial factors to manage physical demands, ensure mental health, and thereby mitigate musculoskeletal pain.